E essa é a minha opinião: para o estudo da emergência da escrita argumentativa. - Costa, Ana Luísa (2018)
In this article, we present an empirical study on early argumentative writing, in opinion texts written by children of the 2nd and 4th grade (1st cycle of basic education). The analysis of discourse and linguistic properties shows early skills in written argumentation. These results call into question the Portuguese teaching guidelines, which only begin providing for the writing of opinion texts in the 5th grade. This study also brings to light the conclusions of similar studies (Brassart, 1990, Leal & Morais, 2006) and contributes to the characterization of writing development and linguistic awareness in the initial school years.